Effects of Organic Fertilizer and Sulfur- and Zinc-Enriched NPK Fertilizer on the Growth and Yield of White Eggplant (Solanum melongena L.) - Mahardika, Ida Bagus Komang; Situmeang, Yohanes Parlindungan; Prakerti, Ni Luh Adelia Darma (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study investigates the effects of organic fertilizer and NPK fertilizer enriched with sulfur (S) and zinc (Zn) on the growth and yield of white eggplant (Solanum melongena L.). A factorial experiment was conducted to evaluate vegetative and generative responses under varying fertilizer dosages. Results demonstrated that both fertilizers independently exerted significant effects on vegetative growth, particularly plant height and leaf number. The optimal treatments—30 tons/ha of organic fertilizer (O3) and 600 kg/ha of NPK fertilizer (Z3)—produced the tallest plants (62.95 cm) and the highest leaf count (14.78 leaves), indicating enhanced photosynthetic capacity and plant vigor. Generative development also improved with increased fertilizer dosages. Treatment O3 yielded 23.00 flowers and 14.67 fruits per plant, a 13.83% increase over the lowest dose. Treatment Z3 resulted in 24.00 flowers and 56.07 fruits per plant, an 8.47% increase compared to Z1, highlighting the critical role of Zn and S in reproductive organ formation. Furthermore, fresh fruit weight significantly increased under both treatments, with O3 producing 1,710.00 g and Z3 yielding 1,768.78 g per plant—representing 13.85% and 19.63% improvements, respectively. These findings confirm that precise fertilizer combinations can substantially enhance the productivity and quality of white eggplant harvests